The association between outcomes and body mass index in patients with acute respiratory distress syndrome. (19th April 2021) - Chen, Ziying; Huang, Xu; Lu, Haining; Deng, Wang; Huang, Linna; Wu, Dawei; Wang, Daoxin; Zhan, Qingyuan
Abstract: Introduction: Limited information exists about the relationship between body mass index (BMI) and the outcome of acute respiratory distress syndrome (ARDS). Objective: To evaluate the hospital mortality of patients with ARDS in relation to BMI. Materials and methods: We conducted a retrospective, multicenter study including patients with ARDS. ARDS was defined according to the Berlin criteria. Body weight and height were obtained to calculate BMI. The primary outcome was in‐hospital mortality. Secondary outcomes were intensive care unit (ICU) mortality, invasive positive pressure ventilation (IPPV) free days within 28 days and length of stays in the ICU and hospital. Results: Among 523 patients, 28 (5%) were underweight (BMI <18.5 kg/m 2 ), 299 (57%) were normal weight (BMI 18.5‐24.9 kg/m 2 ), 159 (30%) were overweight (BMI 25‐29.9 kg/m 2 ) and 37 (7%) were obese (BMI ≥30 kg/m 2 ). Increasing BMI was associated with younger age ( P  = 0.017), hypertension ( P  = 0.003) and diabetes ( P  = 0.02). Compared with normal weight, being overweight and obese resulted in lower mortality regardless of whether in the hospital ( P  = 0.019) or ICU ( P  = 0.044). However, after risk adjustment, only obesity was associated with lower hospital mortality (OR 0.393, 95% CI 0.169‐0.914, P  = 0.030). With the increase of BMI, the in‐hospital mortality and ICU mortality of ARDS dropped gradually (from 57.1% to 24.3%, P  = 0.021, and from 53.6% to 24.3%, P  = 0.035). Conclusions: Obesity is associated with lower mortality in patients with ARDS. With the increase of BMI, the mortality of ARDS drops gradually.